Size Effects at Ultrasonic Treatment of Nanoporous Carbon and Improved Characteristics of Supercapacitors on Its Base - Balaban, O.V.; Venhryn, B.Ya.; Grygorchak, I.I.; Mudry, S.I.; Kulyk, Yu.O.; Rachiy, B.I.; Lisovskiy, R.P. (Наносистеми, наноматеріали, нанотехнології, 2014)
As shown, the common characteristic for nanoporous carbons obtained from different types of natural raw materials is so called fractal geometry, which changing is substantially reflected on the process of capacitive energy storage in an electric double layer (EDL) formed at the boundary between the carbon material and the electrolyte (KOH 30% aqueous solution). Relationship between the parameters of fractality and features of ultrasonic influence of carbon on the electronic structure and the structure of the EDL is investigated and results in establishing conditions to achieve improved performance characteristics of supercapacitors based on them.